The Simulation and Design of High Subsonic Wing Aircraft - Prasetyo Edi (ICON-CSE, 2014)
This paper intends to present the application of Computational Fluid Dynamic (CFD) on the simulation and design of high subsonic wing of transport aircraft. The computation was performed using RAMPANT, an unstructured, multigrid flow solver. A 2-D and 3-D model of the wing was created using CATIA (2D and 3D modeling). A corresponding grid was created using preBFC and TGrid. The paper describes the technique of creating the grid and using the CFD on the wing design process. It then discusses the benefits and penalties of using the above tools. Description is then given in using the aerodynamic analysis result to optimize the wing. It concludes with a discussion of the results and recommendations for future work.